Tinjauan Hukum Terhadap Notaris yang Melakukan Tindak Pidana Penggelapan Atas Penerimaan Uang Pembayaran Pajak Penghasilan (Pph) dan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) : Studi Putusan Nomor 1035/Pid.B/2021/PN.Kis - Edi Suranta Sembiring (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Notary is a public official who is appointed and given authority by the Government to provide services to the community in terms of making authentic deeds, where this authentic deed is a deed made by or before a Notary according to the form and procedures applied in Law Number 2 of 2014 concerning Amendments to Law 30 of 2004 concerning the Position of Notary. In normative legal research or also called library legal research, namely legal research conducted by examining library materials or secondary data only. This legal research uses primary legal materials, namely legal materials that have binding force and are generally applicable. Secondary legal materials, such as books, research results from legal circles related to this legal research. Tertiary legal materials, namely legal dictionaries, the Great Dictionary of the Indonesian Language, encyclopedias. The notary's liability for abuse of authority related to Income Tax (Pph) and Land and/or Building Acquisition Fee (BPHTB) received in the process of changing the name of the land certificate is that he will be held accountable according to the code of ethics regarding the trust given by his client to pay the BPHTB tax but not paid. The legal efforts of the injured party related to Income Tax (Pph) and Land and/or Building Acquisition Fee (BPHTB) carried out by the notary in connection with the legal process in the transfer of land rights, the notary is asked to be held accountable civilly with a lawsuit for unlawful acts for compensation. The judge's consideration of the notary who abused his position is based on the decision of the Kisaran District Court Number 1035/Pid.B/2021/PN.Kis, which includes the aggravating circumstances being that the defendant was unprofessional in his position as a notary, and the mitigating circumstances being that the defendant openly admitted his actions, the defendant has reconciled with the victim PT. Multimas Nabati Asahan and the defendant has compensated PT. Multimas Nabati Asahan.